Criminal Law Enforcement Model for the Crime of Killing Protected Elephants (Elephas Maximus) - Saifuddin, Saifuddin; Hanim, Lathifah (Jurnal Hukum Khaira Ummah, 2025)
The purpose of this study is to analyze and explain the criminal law enforcement model for the crime of killing protected elephants (Elephas maximus) in Aceh Jaya, and the inhibiting factors and efforts to enforce criminal law against the crime of killing protected elephants (Elephas maximus) in Aceh Jaya. This study uses an empirical juridical research method with a qualitative approach. Based on the research that has been conducted, it can be concluded that the model of Criminal Law Enforcement for the Crime of Killing Protected Elephants (Elephas Maximus) in Aceh Jaya is using the Due Process Model. This is because the court has provided space for each defendant to present their defense before the trial as a form of protection of the human rights of the defendants and the judiciary also applies the principle of presumption of innocence. Factors that inhibit law enforcement, reviewed from Court Decision Number 51/Pid.B/LH/2021/PN Cag regarding the killing of protected elephants in Aceh Jaya, namely: a) Lack of personnel from the Natural Resources Conservation Agency (BKSDA); b) Lack of community participation. Criminal penalties against the perpetrators are considered insufficient to deter them. Other law enforcement alternatives include revoking permits for plantation activities, particularly those within conservation areas.